Preparation method of anti-static ceramic material
Through the use of 钇 stable oxidation and other raw materials and specific process steps in the preparation of ceramic materials, it solves the problem of poorly combined with poor, high energy consumption and cost of ceramic materials during the preparation process, and realizes the good anti -static performance of ceramic materials and anti -static performance and Excellent physical and chemical properties.
Patent Information
- Application Number
- CN202411487869.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
During the preparation process, existing anti-static ceramic materials have problems such as poor bonding of conductive materials with ceramic substrates, high energy consumption, high cost, low product strength and hardness, and poor wear resistance.
Using raw materials such as yttrium-stabilized zirconia, zinc oxide, ferric oxide, tin oxide and titanium dioxide, it is mixed through ball milling, drying, ball milling crushing, granulation, preforming, secondary compaction, degreasing pre-sintering and buried powder sintering. Steps to prepare ceramic materials ensure that the raw materials are fully mixed and ground to increase the density and strength of the material.
The ceramic material has achieved good anti-static properties, excellent physical and chemical properties, strength of 300-800MPa, hardness HV600-900, good wear resistance, stable chemical properties, high temperature resistance, corrosion resistance, and reduced energy consumption and production costs.
Smart Images

Figure CN119350020A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic material preparation, in particular to a method for preparing an antistatic ceramic material. Background Art
[0002] In modern science and technology and industrial production, static electricity often brings many adverse effects. Antistatic ceramic material, as a special material, can effectively solve these problems. It has good antistatic properties, which can prevent the accumulation and release of static electricity from causing harm to the surrounding environment and equipment. At the same time, it also has stable chemical properties, high strength, wear resistance, high temperature resistance, and corrosion resistance, so that it can meet the strict requirements of different industries for material performance in electronic ceramics, functional ceramics, bioceramics and structural ceramics.
[0003] In order to solve the problem that ceramic materials are prone to static electricity, the existing anti-static ceramics achieve the anti-static purpose by combining external conductive materials with the ceramic matrix. However, this method has many shortcomings. On the one hand, the conductive material is not well combined with the ceramic matrix and has poor dispersion, which affects the anti-static effect and the overall performance of the material. On the other hand, there are defects in its preparation process. The sample needs to be sintered at high temperature and the sintering time is long, which not only increases energy consumption and production costs, but also may lead to more defects in the product after firing. In addition, the proportion of conductive powder is relatively large, which further increases the material cost.
[0004] However, during the actual use of the above equipment, the antistatic ceramic may have low strength and hardness and poor wear resistance. Therefore, we propose a method for preparing an antistatic ceramic material. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an antistatic ceramic material to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing an antistatic ceramic material comprises the following steps:
[0008] S1. Weighing and mixing raw materials by ball milling: Weigh yttrium-stabilized zirconium oxide, zinc oxide, ferric oxide, tin oxide, and titanium dioxide in proportion, put them into a ball mill, add zirconium oxide grinding balls, deionized water, and a dispersant, then add a binder, and continue to mix by ball milling to complete the batching.
[0009] S2. Ingredient drying: The obtained ingredients are placed in a tray and dried in a drying oven.
[0010] S3. Ball milling and crushing of the dried ingredients: ball milling and crushing of the dried ingredients.
[0011] S4, granulation and powder making: granulation is performed using a 60-mesh sieve to complete the powder making and obtain zirconium oxide antistatic ceramic powder.
[0012] S5. Preforming: Put the zirconium oxide antistatic ceramic powder into a dry pressed steel mold for preforming.
[0013] S6. Secondary compaction: The preformed green blank is packaged with a plastic sealing machine and then placed in a cold isostatic press for secondary compaction to obtain a high-strength and high-density zirconia antistatic ceramic green blank.
[0014] S7, degreasing and pre-sintering: put the obtained zirconia antistatic blank into the degreasing furnace for degreasing and pre-sintering, and sinter to remove the binder.
[0015] S8, sintering: put the pre-fired product into the sintering furnace to complete the sintering, adopt the buried powder sintering method, the buried powder is a mixed powder of zinc oxide and aluminum oxide, and obtain large-sized zirconium oxide antistatic ceramics.
[0016] Preferably, the method further includes the following steps: weighing yttrium-stabilized zirconium oxide, zinc oxide, ferric oxide, tin oxide, and titanium dioxide in proportion: the selection and proportion of these raw materials are determined after multiple experiments and studies, and are crucial for the final preparation of a ceramic material with good antistatic properties and physical and chemical properties.
[0017] Put the above raw materials into a ball mill, and then add zirconium oxide grinding balls, deionized water and dispersant, material: ball: water = 1:2:0.6, ball mill for 24 hours, speed 60r / min. This specific material, ball, water ratio and ball milling time and speed are to ensure that the raw materials can be fully mixed and ground during the ball milling process, so that the raw materials can fully contact and undergo physical and chemical reactions to achieve an ideal mixing effect.
[0018] Then add the adhesive to the ball-milled material and continue the ball-milling for 4 hours. The purpose of continuing the ball-milling after adding the adhesive is to make the adhesive evenly distributed in the raw materials and fully combine with other raw materials to ensure that the final product has good structural stability. The dispersant includes at least one of ammonium citrate, polyvinyl pyrrolidone and polyethylene glycol. These dispersants have good dispersing properties, can reduce the surface tension between the raw materials, make the raw materials easier to disperse in the solution, thereby promoting uniform mixing of the raw materials, and taking out the slurry to complete the batching.
[0019] Preferably, the method further comprises the following steps:
[0020] The obtained ingredients are put into a dish and dried in a drying oven with the temperature set at 100°C and the drying time being 6 hours. The drying temperature of 100°C and the drying time of 6 hours are selected because under this condition, the moisture in the ingredients can be effectively removed without causing adverse effects on the raw materials, such as causing certain components in the raw materials to decompose or deteriorate. The dried ingredients are ball-milled at a speed of 200r / min for 5 minutes. The purpose of ball milling is to further refine the dried ingredients and make their particles more uniform and fine. The speed of 200r / min and the time of 5 minutes are appropriate parameters determined by experiments, which can ensure that the ingredients achieve the ideal refinement effect during the ball milling process. Then a 60-mesh sieve is used for granulation to complete the powder making and obtain zirconium oxide antistatic ceramic powder. Granulation is to make the refined ingredients into particles of suitable size. The 60-mesh sieve can screen out particles that meet the requirements. The size and shape of these particles have an important influence on the subsequent molding operation. Suitable particles can ensure that the ceramic material is more uniform and stable during the molding process.
[0021] Preferably, the method further comprises the following steps:
[0022] The prepared zirconia antistatic ceramic powder is placed in a dry pressing steel mold for preforming. The dry pressing pressure is 10-50MPa. Preforming within this pressure range can make the ceramic powder initially formed in the mold and have a certain density and strength. The preformed blank is then packaged with a plastic sealing machine and placed in a cold isostatic press for secondary compaction. The pressure is greater than 150MPa. The secondary compaction is to further improve the density and strength of the blank. By applying a larger pressure, the blank is made denser, thereby improving the physical properties of the final product, such as strength and hardness. Then, a high-strength and high-density zirconia antistatic ceramic blank is obtained.
[0023] Preferably, the method further comprises the following steps:
[0024] The obtained zirconia antistatic biscuit is put into the degreasing furnace for degreasing and pre-sintering, and the binder is sintered to remove the binder. The debinding heating rate is 0.1-15℃ / min, the debinding temperature is 1150℃, and the temperature is kept for 1-5h. The purpose of degreasing and pre-sintering is to remove the binder in the biscuit. Under this specific heating rate, debinding temperature and holding time conditions, the binder can be effectively removed while avoiding adverse effects on the biscuit, such as cracking of the biscuit due to too fast a heating rate, or wasting energy due to too long a holding time.
[0025] Preferably, the method further comprises the following steps:
[0026] The pre-fired product is placed in a sintering furnace to complete sintering. The sintering temperature is 1300°C-1450°C, the heating rate is 0.2-10°C / min, and the insulation is 1-5h. The sintering method is buried powder sintering. The buried powder of the buried powder sintering is a mixed powder of zinc oxide and aluminum oxide to obtain large-size zirconium oxide antistatic ceramics. The mass percentage of zinc oxide in the mixed powder of zinc oxide and graphite is 30% to 55%.
[0027] Sintering within this temperature and heating rate range and using the powder-embedded sintering method can further densify the ceramic green body and improve its physical properties. Appropriate powder-embedded composition and proportion can improve the sintering effect of the ceramic, improve the quality and dimensional stability of the ceramic, and ultimately obtain large-sized zirconia antistatic ceramics.
[0028] Preferably, the ferric oxide is a colorant, which is partially reduced to ferrous oxide to form ferroferric oxide, which appears black;
[0029] Ferric oxide plays a dual role in the preparation of antistatic ceramic materials. On the one hand, it participates in the preparation of ceramic materials as a raw material. On the other hand, it acts as a colorant and is partially reduced to ferrous oxide under certain conditions to form ferroferric oxide, making the ceramic material black. This color change can provide more options for the appearance design of ceramic materials, but it may also have a certain impact on some of its properties, which needs to be considered in the preparation process.
[0030] Preferably, the titanium dioxide and tin oxide are sintering aids to reduce the sintering temperature;
[0031] Titanium dioxide and tin oxide play an important role in the preparation of ceramic materials. As sintering aids, they can reduce the sintering temperature, which is of great significance for saving energy and improving production efficiency. At the same time, lowering the sintering temperature may also affect other properties of ceramic materials, such as crystal structure and density, which need to be comprehensively considered during the preparation process.
[0032] Preferably, the dispersant includes at least one of ammonium citrate, polyvinyl pyrrolidone and polyethylene glycol, and its function is to promote uniform mixing of the raw materials;
[0033] These dispersants play a key role in the raw material mixing process. They can reduce the surface tension between the raw materials and make the raw materials easier to disperse in the solution, thereby ensuring that the raw materials can be mixed more evenly during the ball milling process, providing a guarantee for the preparation of high-quality ceramic materials.
[0034] Preferably, the binder is used to bind the raw materials together to ensure the molding and structural stability of the ceramic;
[0035] Adhesives are indispensable in the preparation process of ceramic materials. They are used to combine various raw materials together to ensure the molding and structural stability of ceramic materials. By fully combining with other raw materials, adhesives can form a continuous network structure to fix the raw material particles together and prevent loosening or cracking during processing.
[0036] The yttrium-stabilized zirconia plays a key role in the raw material system, and its content range and preparation method ensure that the ceramic has good physical and chemical properties.
[0037] Yttrium-stabilized zirconia is an important component of antistatic ceramic materials. The determination of its content range is the result of many experiments and studies. It can ensure that the ceramic material has good physical and chemical properties while having antistatic properties. Its preparation method includes weighing raw materials, mixing, drying, sintering, solid solution and screening. The strict implementation of these steps can ensure the quality and stability of yttrium-stabilized zirconia, thereby providing a solid foundation for the performance of the entire ceramic material.
[0038] Compared with the prior art, the present invention provides a method for preparing an antistatic ceramic material, which has the following beneficial effects:
[0039] 1. The preparation method of the antistatic ceramic material, through precise raw material ratio and strict process control, makes the final antistatic ceramic material have good antistatic performance, and its volume resistance is 10 4 -10 9 Ohms, which can effectively avoid static electricity problems. At the same time, the material has excellent physical and chemical properties, strength between 300-800MPa, hardness HV600-900, good wear resistance; stable chemical properties, high temperature resistance, corrosion resistance, good finish and stable resistance.
[0040] 2. The preparation method of the antistatic ceramic material adopts a specific dispersant in the raw material mixing process to reduce the surface tension between the raw materials and promote uniform mixing. This efficient mixing method not only saves time but also improves the utilization rate of raw materials. Titanium dioxide and tin oxide are used as sintering aids to reduce the sintering temperature. Under the sintering temperature range of 1300℃-1450℃ and the heating rate of 0.2-10℃ / min, compared with the traditional process, it can reduce energy consumption and improve production efficiency.
[0041] 3. The preparation method of the antistatic ceramic material, during the molding process, the ceramic powder is first preformed under a pressure of 10-50MPa to give it a certain density and strength, and then secondary compaction is performed under a pressure greater than 150MPa. This secondary compaction operation further improves the density and strength of the green blank, and the physical properties of the final product are better, preventing looseness or cracking during the processing process, and ensuring that the ceramic material has good structural stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 A schematic diagram of the structure of an overall process module of the present invention;
[0043] Figure 2 It is a schematic diagram of the overall structure of a method for preparing an antistatic ceramic material of the present invention;
[0044] Figure 3 This is a schematic diagram of the structure of the raw material preparation and mixing module of the present invention;
[0045] Figure 4 It is a structural schematic diagram of the batching processing module of the present invention;
[0046] Figure 5 It is a structural schematic diagram of the molding module of the present invention;
[0047] Figure 6 It is a schematic diagram of the structure of the debinding and sintering module of the present invention. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] See also Figure 1 - Figure 6 , the present invention provides a technical solution:
[0050] A method for preparing an antistatic ceramic material Raw material preparation
[0051] Raw material selection and proportion determination:
[0052] According to the required performance of antistatic ceramic materials, after a lot of experiments and research, it is determined that the raw materials include yttrium-stabilized zirconium oxide, zinc oxide, ferric oxide, tin oxide, titanium dioxide and binder. The mass fraction range of each raw material is: yttrium-stabilized zirconium oxide 15%-80%, ferric oxide 5%-50%, tin oxide 1%-10%, zinc oxide 1%-10%, titanium dioxide 0.02%-2%, and the rest is binder.
[0053] For yttrium-stabilized zirconia, if you need to prepare it yourself, follow the steps below:
[0054] Weigh zirconium oxide and yttrium oxide in a specific proportion to ensure accurate weighing and keep the error within a reasonable range.
[0055] Add a dispersant (including at least one of ammonium citrate, polyvinyl pyrrolidone and polyethylene glycol) and an appropriate amount of deionized water, and place in a ball mill. The amount of the dispersant should be sufficient to reduce the surface tension of the raw materials and promote uniform mixing.
[0056] The ball mill runs for 36 hours at a speed that can ensure that the raw materials are fully mixed. During this period, the operating status of the ball mill needs to be monitored to ensure that there are no faults.
[0057] Take out the slurry and dry it at 120℃. The drying equipment must be able to accurately control the temperature to ensure the drying effect without affecting the quality of the raw materials.
[0058] The dried raw materials are placed in a sintering furnace, sintered and solidified at 1200-1300°C, and kept warm for 8-60 hours. The temperature control accuracy of the sintering furnace must be high to ensure sufficient reaction.
[0059] After calcination, the product was sieved through a 200-mesh sieve to obtain yttrium-stabilized zirconia that met the requirements.
[0060] Weighing of raw materials:
[0061] According to the determined ratio, accurately weigh yttrium-stabilized zirconium oxide, zinc oxide, ferric oxide, tin oxide, and titanium dioxide, using weighing instruments with accuracy that meets the requirements to ensure the accuracy of the amount of each raw material.
[0062] In one embodiment of the present invention, the ingredients are mixed:
[0063] Ball milling:
[0064] The weighed raw materials were placed in a ball mill, and zirconium oxide grinding balls, deionized water and dispersant were added in a strict ratio of material: ball: water = 1:2:0.6.
[0065] Use a ball mill, set the speed to 60r / min, and grind for 24 hours. During the grinding process, regularly check the temperature and pressure of the ball mill to ensure that they are within the normal range to ensure that the raw materials are fully mixed and the grinding effect is achieved.
[0066] Adhesive addition and mixing:
[0067] Add adhesive to the raw materials after ball milling for 24 hours. The selection of adhesive should meet the molding and performance requirements of ceramic materials.
[0068] Continue ball milling for 4 hours, keep the operating parameters of the ball mill stable, so that the binder is evenly distributed in the raw materials and fully combined with other raw materials to complete the batching.
[0069] In one embodiment of the present invention, powder making and molding:
[0070] dry:
[0071] Place the ingredients in a suitable tray and use a drying oven to dry them. The temperature of the drying oven is set to 100°C and the drying time is 6 hours. The drying oven should have temperature uniformity to ensure that the ingredients are heated evenly and avoid local overheating or overcooling that affects the quality of the ingredients.
[0072] Ball mill crushing and granulation:
[0073] The dried ingredients are crushed by ball milling. The ball mill speed is set to 200r / min and the crushing time is 5min. During the crushing process, the changes in the ingredient particles are observed to ensure that the refining effect is achieved.
[0074] Then use a 60-mesh sieve to granulate the ingredients after ball milling. When using the sieve, operate in a standardized manner to ensure that particles that meet the requirements are screened out to obtain zirconium oxide antistatic ceramic powder.
[0075] Preform:
[0076] Place the zirconia antistatic ceramic powder into a dry pressed steel mold and use a press to apply a pressure of 10-50MPa for pre-forming. The mold should meet the design requirements, be firmly installed, and apply pressure evenly so that the ceramic powder is initially formed in the mold and has a certain density and strength.
[0077] Secondary compaction:
[0078] The preformed blank is sealed with a plastic sealing machine to prevent gas leakage.
[0079] The packaged green blank is placed in a cold isostatic press and a pressure greater than 150MPa is applied for secondary compaction. The operation of the cold isostatic press should comply with the specifications to ensure that the pressure is applied stably to make the green blank more compact, improve its density and strength, and obtain a high-strength and high-density zirconia antistatic ceramic green blank.
[0080] In one embodiment of the present invention, debinding and sintering
[0081] Degreasing pre-burning:
[0082] Place the zirconia antistatic blank into the degreasing furnace, set the degreasing heating rate to 0.1-15℃ / min, the binder removal temperature to 1150℃, and keep warm for 1-5h. The temperature and heating rate of the degreasing furnace must be controlled with high precision. During the degreasing process, closely observe the blank state to ensure that the binder is effectively removed, and avoid cracking of the blank due to too fast a heating rate, or wasting energy due to too long a holding time.
[0083] sintering:
[0084] The degreased and pre-sintered product is placed in a sintering furnace, the sintering temperature is set to 1300℃-1450℃, the heating rate is 0.2-10℃ / min, and the temperature is kept for 1-5h. The buried powder sintering method is adopted, and the buried powder is a mixed powder of zinc oxide and aluminum oxide, wherein the mass percentage of zinc oxide is 30%-55%. During the sintering process, the sintering furnace temperature and the heating rate are accurately controlled, and the buried powder is evenly distributed, so that the ceramic blank is further densified, its physical properties are improved, and large-sized zirconium oxide antistatic ceramics are obtained.
[0085] S1. Weigh the raw materials and mix them with ball mill:
[0086] Weigh yttrium-stabilized zirconium oxide, zinc oxide, ferric oxide, tin oxide, and titanium dioxide in proportion, put them into a ball mill, add zirconium oxide grinding balls, deionized water, and a dispersant (including at least one of ammonium citrate, polyvinyl pyrrolidone, and polyethylene glycol), material: ball: water = 1:2:0.6, and grind in a ball mill for 24 hours at a speed of 60 r / min. Then add a binder and continue ball milling and mixing for 4 hours to complete the batching.
[0087] S2. Drying of ingredients:
[0088] The obtained ingredients were placed in a tray and dried in a drying oven with the temperature set at 100°C and the drying time being 6 hours.
[0089] S3, ball milling and crushing of ingredients after drying:
[0090] The dried ingredients were ball milled at a speed of 200 r / min for 5 min.
[0091] S4, granulation and powder making:
[0092] Then use a 60-mesh sieve to granulate and complete the powder making to obtain zirconium oxide antistatic ceramic powder.
[0093] S5, Preforming:
[0094] The zirconia antistatic ceramic powder is placed in a dry pressing steel mold for preforming, and the dry pressing pressure is 10-50MPa.
[0095] S6, secondary compaction:
[0096] The preformed green blank is packaged with a plastic sealing machine and then placed in a cold isostatic press for secondary compaction at a pressure greater than 150 MPa to obtain a high-strength and high-density zirconia antistatic ceramic green blank.
[0097] S7, degreasing and pre-burning:
[0098] The obtained zirconia antistatic blank is placed in a degreasing furnace for degreasing and pre-sintering, and the binder is sintered to remove the binder. The debinding heating rate is 0.1-15°C / min, the debinding temperature is 1150°C, and the heat preservation is 1-5h.
[0099] S8, sintering:
[0100] The pre-fired product is placed in a sintering furnace to complete sintering. The sintering temperature is 1300°C-1450°C, the heating rate is 0.2-10°C / min, and the insulation time is 1-5h. The buried powder sintering method is adopted. The buried powder is a mixed powder of zinc oxide and aluminum oxide (the mass percentage of zinc oxide is 30% to 55%) to obtain large-size zirconium oxide antistatic ceramics.
[0101] The above generally describes the present invention in detail, but it is obvious to a person skilled in the art that some modifications or improvements can be made to the present invention. Therefore, modifications or improvements that do not depart from the spirit of the present invention are within the scope of protection of the present invention.
Claims
1. A method for preparing an antistatic ceramic material, characterized in that: The following steps are involved: S1. Weighing and mixing raw materials by ball milling: Weigh yttrium-stabilized zirconium oxide, zinc oxide, ferric oxide, tin oxide, and titanium dioxide in proportion, put them into a ball mill, add zirconium oxide grinding balls, deionized water, and a dispersant, then add a binder, and continue to mix by ball milling to complete the batching. S2. Ingredient drying: The obtained ingredients are placed in a tray and dried in a drying oven. S3. Ball milling and crushing of the dried ingredients: ball milling and crushing of the dried ingredients. S4, granulation and powder making: granulation is performed using a 60-mesh sieve to complete the powder making and obtain zirconium oxide antistatic ceramic powder. S5. Preforming: Put the zirconium oxide antistatic ceramic powder into a dry pressed steel mold for preforming. S6. Secondary compaction: The preformed green blank is packaged with a plastic sealing machine and then placed in a cold isostatic press for secondary compaction to obtain a high-strength and high-density zirconia antistatic ceramic green blank. S7, degreasing and pre-sintering: put the obtained zirconia antistatic blank into the degreasing furnace for degreasing and pre-sintering, and sinter to remove the binder. S8, sintering: put the pre-fired product into the sintering furnace to complete the sintering, adopt the buried powder sintering method, the buried powder is a mixed powder of zinc oxide and aluminum oxide, and obtain large-sized zirconium oxide antistatic ceramics.
2. The method for preparing an antistatic ceramic material according to claim 1, characterized in that: The following steps are also included: Weigh yttrium-stabilized zirconium oxide, zinc oxide, ferric oxide, tin oxide, and titanium dioxide in proportion: the selection and proportion of these raw materials are determined after many experiments and studies, and are crucial to the final preparation of ceramic materials with good antistatic properties and physical and chemical properties. Put the above raw materials into a ball mill, and then add zirconium oxide grinding balls, deionized water and dispersant, material: ball: water = 1:2:0.6, ball mill for 24 hours, speed 60r / min. This specific material, ball, water ratio and ball milling time and speed are to ensure that the raw materials can be fully mixed and ground during the ball milling process, so that the raw materials can fully contact and undergo physical and chemical reactions to achieve an ideal mixing effect. Then add the adhesive to the ball-milled material and continue the ball-milling for 4 hours. The purpose of continuing the ball-milling after adding the adhesive is to make the adhesive evenly distributed in the raw materials and fully combine with other raw materials to ensure that the final product has good structural stability. The dispersant includes at least one of ammonium citrate, polyvinyl pyrrolidone and polyethylene glycol. These dispersants have good dispersing properties, can reduce the surface tension between the raw materials, make the raw materials easier to disperse in the solution, thereby promoting uniform mixing of the raw materials, and taking out the slurry to complete the batching.
3. The method for preparing an antistatic ceramic material according to claim 1, characterized in that: The following steps are also included: The obtained ingredients are put into a dish and dried in a drying oven with the temperature set at 100°C and the drying time being 6 hours. The drying temperature of 100°C and the drying time of 6 hours are selected because under this condition, the moisture in the ingredients can be effectively removed without causing adverse effects on the raw materials, such as causing certain components in the raw materials to decompose or deteriorate. The dried ingredients are ball-milled at a speed of 200r / min for 5 minutes. The purpose of ball milling is to further refine the dried ingredients and make their particles more uniform and fine. The speed of 200r / min and the time of 5 minutes are appropriate parameters determined by experiments, which can ensure that the ingredients achieve the ideal refinement effect during the ball milling process. Then a 60-mesh sieve is used for granulation to complete the powder making and obtain zirconium oxide antistatic ceramic powder. Granulation is to make the refined ingredients into particles of suitable size. The 60-mesh sieve can screen out particles that meet the requirements. The size and shape of these particles have an important influence on the subsequent molding operation. Suitable particles can ensure that the ceramic material is more uniform and stable during the molding process.
4. The method for preparing an antistatic ceramic material according to claim 1, characterized in that: The prepared zirconia antistatic ceramic powder is placed in a dry pressing steel mold for preforming. The dry pressing pressure is 10-50MPa. Preforming within this pressure range can make the ceramic powder initially formed in the mold and have a certain density and strength. The preformed blank is then packaged with a plastic sealing machine and placed in a cold isostatic press for secondary compaction. The pressure is greater than 150MPa. The secondary compaction is to further improve the density and strength of the blank. By applying a larger pressure, the blank is made denser, thereby improving the physical properties of the final product, such as strength and hardness. Then, a high-strength and high-density zirconia antistatic ceramic blank is obtained.
5. The method for preparing an antistatic ceramic material according to claim 1, characterized in that: The obtained zirconia antistatic biscuit is put into a degreasing furnace for degreasing and pre-sintering, and the binder is sintered to remove the binder, and the debinding heating rate is 0.1-15°C / min, the debinding temperature is 1150°C, and the temperature is kept for 1-5 hours. The purpose of degreasing and pre-sintering is to remove the binder in the biscuit. Under the conditions of this specific heating rate, debinding temperature and holding time, the binder can be effectively removed while avoiding adverse effects on the biscuit, such as cracking of the biscuit due to too fast a heating rate, or wasting energy due to too long a holding time.
6. The method for preparing an antistatic ceramic material according to claim 1, characterized in that: The pre-fired product is placed in a sintering furnace to complete sintering, the sintering temperature is 1300°C-1450°C, the heating rate is 0.2-10°C / min, and the insulation is 1-5h. The sintering method is buried powder sintering, and the buried powder of the buried powder sintering is a mixed powder of zinc oxide and aluminum oxide to obtain large-size zirconium oxide antistatic ceramics. The mass percentage of zinc oxide in the mixed powder of zinc oxide and graphite is 30% to 55%. Sintering within this temperature and heating rate range and using the powder-embedded sintering method can further densify the ceramic green body and improve its physical properties. Appropriate powder-embedded composition and proportion can improve the sintering effect of the ceramic, improve the quality and dimensional stability of the ceramic, and ultimately obtain large-sized zirconia antistatic ceramics.
7. The method for preparing an antistatic ceramic material according to claim 1, characterized in that: The ferric oxide is a coloring agent, which is partially reduced to ferrous oxide to form ferroferric oxide, which appears black; Ferric oxide plays a dual role in the preparation of antistatic ceramic materials. On the one hand, it participates in the preparation of ceramic materials as a raw material. On the other hand, it acts as a colorant and is partially reduced to ferrous oxide under certain conditions to form ferroferric oxide, making the ceramic material black. This color change can provide more options for the appearance design of ceramic materials, but it may also have a certain impact on some of its properties, which needs to be considered in the preparation process.
8. The method for preparing an antistatic ceramic material according to claim 1, characterized in that: The titanium dioxide and tin oxide are sintering aids to reduce the sintering temperature; Titanium dioxide and tin oxide play an important role in the preparation of ceramic materials. As sintering aids, they can reduce the sintering temperature, which is of great significance for saving energy and improving production efficiency. At the same time, lowering the sintering temperature may also affect other properties of ceramic materials, such as crystal structure and density, which need to be comprehensively considered during the preparation process.
9. The method for preparing an antistatic ceramic material according to claim 1, characterized in that: The dispersant includes at least one of ammonium citrate, polyvinyl pyrrolidone and polyethylene glycol, and its function is to promote uniform mixing of the raw materials; These dispersants play a key role in the raw material mixing process. They can reduce the surface tension between the raw materials and make the raw materials easier to disperse in the solution, thereby ensuring that the raw materials can be mixed more evenly during the ball milling process, providing a guarantee for the preparation of high-quality ceramic materials.
10. The method for preparing an antistatic ceramic material according to claim 1, characterized in that: The binder is used to bind the raw materials together to ensure the molding and structural stability of the ceramic; Adhesives are indispensable in the preparation process of ceramic materials. They are used to combine various raw materials together to ensure the molding and structural stability of ceramic materials. By fully combining with other raw materials, adhesives can form a continuous network structure to fix the raw material particles together and prevent loosening or cracking during processing. The yttrium-stabilized zirconia plays a key role in the raw material system, and its content range and preparation method ensure that the ceramic has good physical and chemical properties. Yttrium-stabilized zirconia is an important component of antistatic ceramic materials. The determination of its content range is the result of many experiments and studies, which can ensure that the ceramic material has antistatic properties while also having good physical and chemical properties. Its preparation method includes weighing raw materials, mixing, drying, sintering and solid solution, and screening steps. The strict implementation of these steps can ensure the quality and stability of yttrium-stabilized zirconia, thereby providing a solid foundation for the performance of the entire ceramic material.